Textuality and Knowledge : Essays - Shillingsburg, Peter L. (Book collections on Project MUSE., 2017)
"A collection of essays exploring the role of textual studies in understanding and editing texts, and in understanding the historical developments and cultural differences in editorial and archival systems"--Provided by publisher